Combined use of an electrostatic precipitator and a high‐efficiency particulate air filter in building ventilation systems: Effects on cardiorespiratory health indicators in healthy adults. (24th January 2018) - Day, D. B.; Xiang, J.; Mo, J.; Clyde, M. A.; Weschler, C. J.; Li, F.; Gong, J.; Chung, M.; Zhang, Y.; Zhang, J.
Abstract: High‐efficiency particulate air (HEPA) filtration in combination with an electrostatic precipitator (ESP) can be a cost‐effective approach to reducing indoor particulate exposure, but ESPs produce ozone. The health effect of combined ESP‐HEPA filtration has not been examined. We conducted an intervention study in 89 volunteers. At baseline, the air‐handling units of offices and residences for all subjects were comprised of coarse, ESP, and HEPA filtration. During the 5‐week long intervention, the subjects were split into 2 groups, 1 with just the ESP removed and the other with both the ESP and HEPA removed. Each subject was measured for cardiopulmonary risk indicators once at baseline, twice during the intervention, and once 2 weeks after baseline conditions were restored. Measured indoor and outdoor PM2.5 and ozone concentrations, coupled with time‐activity data, were used to calculate exposures. Removal of HEPA filters increased 24‐hour mean PM2.5 exposure by 38 (95% CI: 31, 45) μg/m 3 . Removal of ESPs decreased 24‐hour mean ozone exposure by 2.2 (2.0, 2.5) ppb. No biomarkers were significantly associated with HEPA filter removal. In contrast, ESP removal was associated with a −16.1% (−21.5%, −10.4%) change in plasma‐soluble P‐selectin and a −3.0% (−5.1%, −0.8%) change in systolic blood pressure, suggesting reduced cardiovascular risks.